Contributing to evidence-based policy making in the Nile BDC—group feedback - Puskur, Ranjitha (International Livestock Research Institute, 2011)
In early May 2011, people working on the Nile Basin Development Challenge (http://nilebdc.org) met in Addis Ababa in a 'science and reflection workshop'. Session 2 of the workshop examined institutional and other processes that are key to success of the overall program. In this video, Ranjitha Puskur (ILRI) reports from small group discussions on how ways to ensure our evidence is credible, relevant. practical and operationally useful, how and what kind of feedback processes and networks should we develop to communicate our messages, and how we go about understanding policy better.